The Effect of Environmental Education, Consumer Awareness, and Environmentally Friendly Practices on Plastic Waste Reduction in Indonesia - Wijayanto, Gatot; Mu'min, Halek; Waangsir, Ferry WF; Ardhiyansyah, Andri (West Science Social and Humanities Studies, 2024)
Plastic waste pollution poses a significant environmental challenge in urban areas, including Indonesia. This study investigates the impact of environmental education, consumer awareness, and environmentally friendly practices on plastic waste reduction in Indonesia using a quantitative approach. A structured survey questionnaire was administered to a sample of Indonesia, and data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) regression. The results indicate that environmental education, consumer awareness, and environmentally friendly practices have a significant positive effect on plastic waste reduction. Specifically, higher levels of environmental education, increased consumer awareness of plastic pollution, and the adoption of environmentally friendly practices are associated with greater reductions in plastic waste. These findings underscore the importance of targeted interventions and collaborative efforts to promote sustainability and environmental stewardship in urban environments facing plastic waste challenges.